History Teacher Readiness in Applying Historical Thinking Skills in Secondary School - Khairunnajwa binti Samsudin; Mohd Mahzan bin Awang; Anuar bin Ahmad (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
This article aims to study on the readiness of history teachers to inculcate historical thinking skills among students. This study focused on four aspects which includes 1) Procedural Knowledge, and 2) Pedagogical Knowledge. Thus, to achieve the purpose of the study, quantitative methods are used. Questionnaires were distributed to 30 history teachers in a secondary school in Batu Pahat district. The results showed that there were no significant differences between teachers who were trained to teach History and those who are not. However, there was a significant difference between teachers with ten years of teaching experience with the readiness of history teachers.